KETIDAKADILAN GENDER DALAM NASKAH DRAMA MATA ADIL MATA TAKDIR KARYA TOTENK MT RUSMAWAN - Echo Dilus; Luluk Isani Kulup (Universitas PGRI Adi Buana Surabaya, 2020)
The purpose of this study is to describe gender injustice in the drama script Mata Adil Mata Takdir by Totenk MT Rusmawan. The theory used in this research is Fakih's theory which refers to gender injustice towards women as a support in his study. The method used in this study is a qualitative research method. Data collection techniques use words, sentences, and paragraphs. The technical analysis of the data used is reading, interpreting and concluding. The results of the research found in the drama script Mata Adil Mata Takdir there are gender injustices experienced by female characters by men contained in the drama script. Women leaders experience gender injustice by men in the form of job impoverishment, women 's numbering, and violence against women in terms of physical, psychological and rape violence. Conclusions in this study the forms of gender injustice in the lives of women leaders Gender differences have given birth to various injustices, both men and especially against women. injustice is a system and structure of both men and women become victims of the system. Suggestions in this research can be useful for the development of teaching Indonesian language and literature in understanding gender injustice contained in literary works, especially drama scripts.